Vicia faba-PGPB association improves soil health as a sustainable strategy to remediate moderately Pb and Cd contaminated soils - Omar Saadani; Souhir Abdelkrim; Wael Taamalli; Imen Challougui Fatnassi; Khedhiri Mannai; Moez Jebara; Salwa Harzalli Jebara (PLoS ONE, 2026)
Phytoremediation is an eco-friendly strategy for heavy metal bioremediation. This study focuses on assessing the potential of faba bean- plant growth promoting bacteria symbiosis in phytoremediation and soil fertility improvement of HMs contaminated soils. Vicia faba L. var. minor Saber 02 was inoculated with a consortium of three efficient and HMs resistant PGPB ( Rhizobium sp. CCNWSX0481, R. leguminosarum bv. viciae and Pseudomonas sp.) and cultivated in soil treated with Cd and Pb to establish three contamination levels: uncontaminated (S1), moderately contaminated (S2; 2 mg kg -1 Cd and 100 mg kg -1 Pb), and highly contaminated (S3; 4 mg kg -1 Cd and 200 mg kg -1 Pb). Bacterial inoculation enhanced plant growth and metal uptake, most significantly in the moderately contaminated soil (S2). An increase in shoot dry weight and nodule dry weight was observed after bacterial inoculation mostly in the moderately contaminated soil S2. Furthermore, the effect of bacterial inoculation was particularly pronounced in S2 soil, resulting in significant increases in Pb and Cd accumulation in the shoots by 66% and 441%, respectively, compared to the uninoculated plants. Similarly, inoculated plants grown in S2 soil exhibited substantially higher total heavy metal contents than the uninoculated plants, reaching 179% for Pb and 319% for Cd, respectively. This increase was associated with an enhancement in the concentration of non-protein thiols, particularly in S2 soil, where inoculation increased root NPT levels by 49% compared to the uninoculated plants. Nevertheless, HMs induced a significant increase in roots enzyme such as superoxide dismutase, catalase and glutathione reductase. The inoculation further enhancing their activities essentially in S2. Moreover, PGPB considerably reduced total Pb as well as both the total and available fractions of Cd, mainly in S2 soil and increased total nitrogen and available phosphorus content, urease and β-glucosidase activities. The obtained results highlight the effectiveness of V. faba L var. minor Saber 02- PGPB symbiosis in the reclamation of moderately Pb and Cd contaminated soils. The bacterial consortium could be used as biofertilizer to improve soil quality of Cd/Pb contaminated sites.